Implementing “Superlary Game” To Improve Students’ Vocabulary Mastery - Intan Maulida Rizikiya; Hesti Puspita Sari; Nita Susanti; Supriyono Supriyono (Jurnal Lingua Idea, 2022)
This research is aimed to overcome the problem in the classroom by improving students’ vocabulary mastery through game. The research is conducted in SMAN 1 Kademangan for grade tenth of MIPA 1. The game applied in this research was made by Wahyu Dwi Lestari (2020). It is a “Superlary game” game stand for Escapade game. To cater to a new way of overcoming this issue, classroom action research is focusing on intensifying the students’ vocabulary mastery through the game. The research instruments were pre-test and post-test which were analyzed using an independent sample t-test. Furthermore, the results obtained that the results of the post-test test of 84 are greater than the pre-test of 63. This means that the Superlary game application is effective for improving vocabulary mastery and learning achievement of students of class X MIPA SMAN 1 Kademangan Blitar. This finding shows that students show a very good increase in vocabulary enrichment in one cycle. Therefore, it can be concluded that the Superlary game application can be used effectively by teachers as an alternative application for teaching and learning vocabulary mastery, especially for the basic competencies of historical events. For the future researchers can use the results of this research as the first step to examine the effectiveness of students using “Superlary game” or even create similar games with different themes.